Correlation of myopia with age, axial length and anterior chamber depth - Kaur, Avleen; Kai, Sanjay; Raina, Bhavani (International Journal of Research in Medical Sciences, 2023)
Background: Uncorrected myopia or near sightedness is a major cause of vision impairment and legal blindness in younger population. It has huge social, psychological, economic and developmental implications. Changes in anterior chamber depth and a significant increase in axial length increase the risk of myopia which can lead to a number of visual complications. Method: This hospital based observational study was conducted in the OPD of department of ophthalmology, government medical college, Jammu over a period of one month from November 2022 to December 2022. A total of 100 patients were involved in this study. Data was interpreted in both descriptive and inferential statistics i.e., frequency and percentage distribution by using SPSS, version 22. Results: It was observed that maximum patients were in the age group of 21-30 years (46%) and male:female ratio was 1.38:1. A positive correlation was found between myopia with axial length and anterior chamber depth (p<0.05). Conclusions: Understanding the role of ocular biometric parameters in myopia is important in not only interpreting the disease pattern but also modelling the pathology and management of ocular diseases. It will go a long way in reducing the burden of myopia and its associated complications.